2021
DOI: 10.1155/2021/5553811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers Associated with Acute Myocardial Infarction by Weighted Gene Coexpression Network Analysis

Abstract: Background. In the general population, acute myocardial infarction (AMI) represents a significant cause of mortality. This study is aimed at identifying novel diagnostic biomarkers to aid in treating and diagnosing AMI. Methods. The Gene Expression Omnibus (GEO) database was explored to extract two microarray datasets, GSE66360 and GSE48060, which were subsequently merged into a single cohort. Both AMI and control samples were analyzed for differentially expressed genes (DEGs), which were subsequently subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Intriguingly, Xie et al inferred that four genes (FN1, CD34, LPL, and WWTR1) were capable of distinguishing STEMI patients from healthy controls and SCAD [37]. Wang et al identified 4 hub genes (LILRB2, TLR2, NCF2, and S100 A9) related to AMI based on three databases (GSE, GSE, and GSE) [38]. However, the identification of RPL9 and RPL26 in our study has not been previously investigated to be related to AMI.…”
Section: Discussioncontrasting
confidence: 56%
“…Intriguingly, Xie et al inferred that four genes (FN1, CD34, LPL, and WWTR1) were capable of distinguishing STEMI patients from healthy controls and SCAD [37]. Wang et al identified 4 hub genes (LILRB2, TLR2, NCF2, and S100 A9) related to AMI based on three databases (GSE, GSE, and GSE) [38]. However, the identification of RPL9 and RPL26 in our study has not been previously investigated to be related to AMI.…”
Section: Discussioncontrasting
confidence: 56%
“…WGCNA can integrate the results of sequencing into biologically significant co-expressed gene modules and analyze the correlation between these gene modules and diseases ( 12 ). Therefore, we used WGCNA to explore modules related to infertile endometriosis.…”
Section: Methodsmentioning
confidence: 99%
“…WGCNA can explore the relationship between diseases and gene modules, which act as significant markers and signaling pathways in the occurrence and development of diseases ( 7 , 8 ). Therefore, WGCNA is frequently employed to investigate the molecular mechanisms of various diseases including coronary artery disease, neuropathic pain, colon adenocarcinoma, and acute myocardial infarction ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, 174 components have been identified from Chuanxiong Rhizoma, among which phthalides and alkaloids would be the main bioactive ingredients for the pharmacological properties (Chen et al, 2018). Our previous clinical trials have already confirmed that PCF could relieve angina pectoris and improve depressive symptoms (Wang et al, 2021). The pharmacological mechanism of PCF concentrates on the regulation of inflammatory response and the neuroendocrinology system.…”
Section: Introductionmentioning
confidence: 99%
“…To systematically identify possible targets and explore the biological mechanism of PCF in depression after AMI, we have performed pharmacoproteomic profiling of the myocardium and hippocampus in rats from the sham, AMI, and PCF groups using label-free liquid chromatography-mass spectrometry (LC-MS/ MS) (Sun et al, 2021). The intersection of differentially expressed proteins (DEPs) in the peri-infarct border zone and hippocampus produces a unique protein, that is S100A9, which has become a topic molecule in the cardiovascular field during these years (Nagareddy et al, 2020;Wang et al, 2021). The role of S100A9 in driving inflammatory response after MI has attracted much attention and has been identified as a potential therapeutic target (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%